Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation